2018
DOI: 10.1111/iju.13863
|View full text |Cite
|
Sign up to set email alerts
|

Male infertility in Sertoli cell‐only syndrome: An investigation of autosomal gene defects

Abstract: Objectives To detect autosomal genetic defects and to determine candidate genes in Sertoli cell‐only syndrome infertile men. Methods Single‐nucleotide polymorphism + comparative genomic hybridization microarray technology was carried out on 39 Sertoli cell‐only syndrome infertile patients in the present study. Array comparative genomic hybridization compares the patient's genome against a reference genome, and identifies uncover deletions, amplifications and loss of heterozygosity. Results A link between defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…2,3 The article by Koc et al reports that the link between defective spermatogenesis genes and SCOS in humans was examined based on single-nucleotide polymorphisms + comparative genomic hybridization array using genomic DNA from 39 SCOS patients. 4 In recent years, DNA microarray technologies have been used to define mutations responsible for infertile phenotypes in men. 5 The authors detected amplifications and deletions in the HOXD9, SYCE1, COL1A1, H19 and KCNQ1 genes.…”
Section: An Investigation Of Autosomal Gene Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 The article by Koc et al reports that the link between defective spermatogenesis genes and SCOS in humans was examined based on single-nucleotide polymorphisms + comparative genomic hybridization array using genomic DNA from 39 SCOS patients. 4 In recent years, DNA microarray technologies have been used to define mutations responsible for infertile phenotypes in men. 5 The authors detected amplifications and deletions in the HOXD9, SYCE1, COL1A1, H19 and KCNQ1 genes.…”
Section: An Investigation Of Autosomal Gene Defectsmentioning
confidence: 99%
“…5 The authors detected amplifications and deletions in the HOXD9, SYCE1, COL1A1, H19 and KCNQ1 genes. 4 It is suggested that these genes might play roles in SCOS progression. Numerous studies have been published on genetic analysis in cases of male infertility.…”
Section: An Investigation Of Autosomal Gene Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian embryo, Sertoli cells play a key role in the onset of male determination and gonadal development [1]. The mechanism of derivation and development of Sertoli cells has a close relevance with some reproductive disorders [2][3][4][5]. However, the molecular pathways in the derivation of Sertoli cells in embryos are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Koc et al . is a retrospective study with patient consent investigating autosomal gene defects in patients with Sertoli cell‐only syndrome (SCOS) . Although azoospermia factor a deletion in the Y chromosome is known to be a genetic cause of SCOS, many other causes of SCOS are still unknown.…”
mentioning
confidence: 99%